a + b + c = 6 a 2 + b 2 + c 2 = 7 8 a 3 + b 3 + c 3 = 4 2 0 a 5 + b 5 + c 5 = x
Find x m o d 5 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
a,b,c are roots of x 3 − 6 x 2 − 2 1 x + 5 8
s1=6,s2=-21,s3=-58 ,so we have x^3-6x-21x+58=0.roots of this equation are solutions for a,b,c. It's obvious x=2 one solution so we can divide with x-2. Then we get x x-4x-29=0,and other two solutions are 2±√33. (d+e)^5+(d-e)^5=(d^5+5d^4 e+10d^3 e^2+10d^2 e^3+5de^4+e^5)+(d^5-5d^4 e+10d^3 e^2-10d^2 e^3+5de^4-e^5)=2 (d^5+10d^3 e^2+5de^4) and for d=2,e=√33 we get (d+e)^5+(d-e)^5=2 (32+80x33+10x33x33)=2 (33-1+33x80+33x330)=2 (33x411-1)=27124 Now we add 2^5 and result is a^5+b^5+c^5=27124+32=27156 27156=50*5430+6,so reminder is 6.
Is this equation worth learning in depth?
Nice solution! I like your use of Newton sums to solve this problem. Very nice indeed.
It's awesome @Chew-Seong Cheong !!!
There is a famous recurrence formula. a^(n+3)+b^(n+3)+c^(n+3)=(a+b+c)(a^(n+2)+b^(n+2)+c^(n+2))-(ab+bc+ca)(a^(n+1)=b^(n+1)+c^(n+1))+ abc(a^(n)+b^(n)+c^(n)) The rest is just plain arithmetic.
Problem Loading...
Note Loading...
Set Loading...
I used the Newton's Sums to solve this.
Let: P 1 = a + b + c P 2 = a 2 + b 2 + c 2 P 3 = a 3 + b 3 + c 3 . . .
S 1 = a + b + c S 2 = a b + b c + c a S 3 = a b c
Then,
P 1 = S 1 = 6
P 2 = S 1 P 1 − 2 S 2 = 7 8 = 6 × 6 − 2 S 2 ⇒ S 2 = − 2 1
P 3 = S 1 P 2 − S 2 P 1 + 3 S 3 = 4 2 0 = 6 × 7 8 + 2 1 × 6 + 3 S 3 ⇒ S 3 = − 5 8
P 4 = S 1 P 3 − S 2 P 2 + S 3 P 1 = 6 × 4 2 0 + 2 1 × 7 8 − 5 8 × 6 = 3 8 1 0
P 5 = S 1 P 4 − S 2 P 3 + S 3 P 2 = 6 × 3 8 1 0 + 2 1 × 4 2 0 − 5 8 × 7 8 = 2 7 1 5 6 = x
Therefore, x m o d 5 0 = 2 7 1 5 6 m o d 5 0 = 6